معوقات التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية من وجهة نظر الأساتذة والإداريين - بن نصر عمار (My University, 2024)
الملخص: هدفت الدراسة إلى التعرف على رؤية الأساتذة والإداريين إلى التعرف على معوقات التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس، والفروق بين هذه الرؤية في ضوء بعض المتغيرات، ولهذا استخدمنا المنهج الوصفي التحليلي لملائمته لطبيعة الموضوع، وللتحقق من الفرض( هناك معوقات (إدارية، تشريعية، تقنية، بشرية ومالية) تعيق التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس) قمنا باستخدام استمارة إستبيانية متكونة من 25 عبارة موزعة على خمسة مجالات على عينة تكونت من (43) من أساتذة وإداريي معهد علوم وتقنيات النشاطات البدنية والرياضية، وعولجت البيانات إحصائيا ببرنامج الحزمة الإحصائية للعلوم الإنسانية إصدار 22، وقد توصلت الدراسة إلى أن معوقات التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس جاءت مرتفعة،كما توصلت الدراسة إلى لا ووجود فروق دالة إحصائيا في رؤية الأساتذة والإداريين للمعوقات التي تعيق التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس تعزى لمتغير السن، والوظيفة (إداري، غير إداري)،في حين أنه توجد فروق دالة إحصائيا في رؤية الأساتذة والإداريين للمعوقات التي تعيق التحول الرقمي بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة سوق أهراس تعزى لمتغير الشهادة، والخبرة المهنية. Summary: The study aimed to identify the vision of professors and administrators to identify the obstacles to digital transformation at the Institute of Science and Technology of Physical and Sports Activities at the University of Souk Ahras, and the differences between this vision in light of some variables. For this reason, we used the descriptive analytical approach due to its suitability to the nature of the subject, and to verify the hypothesis (there are (administrative) obstacles. (legislative, technical, human and financial) hinder the digital transformation at the Institute of Sciences and Technologies of Physical and Sports Activities at the University of Souk Ahras. We used a questionnaire consisting of 25 statements distributed over five areas on a sample consisting of (43) professors and administrators of the Institute of Sciences and Technologies of Physical and Sports Activities, The data was processed statistically using the Statistical Package for the Human Sciences program, version 22. The study concluded that the obstacles to digital transformation at the Institute of Science and Technology of Physical and Sports Activities at the University of Souk Ahras were high. The study also found that there were no and statistically significant differences in the view of professors and administrators of the obstacles that hinder digital transformation at the Institute. Sciences and technologies of physical and sporting activities at the University of Souk Ahras are due to the variable of age and job (administrative, non-administrative), while there are statistically significant differences in the view of professors and administrators of the obstacles that hinder digital transformation at the Institute of Sciences and Technologies of Physical and Sports Actives at the University of Souk Ahras due to the variable of certificate and experience. Professional. résumé : Le but de l'étude est d'identifier la vision des professeurs et des administrateurs, d'identifier les freins à la transformation numérique à l'Institut des Sciences et Technologies Physiques et Sportives de l'Université Souk Ahras, et les différences entre ces visions à la lumière de certaines variables. , c'est pourquoi nous avons utilisé la méthode analytique descriptive pour s'adapter à la nature du sujet, et pour répondre à l'hypothèse (il existe des barrières administratives) (législatives, techniques, humaines et financières) retardant la transformation numérique à l'Institut des Sciences et Technologies de Activités Physiques et Sportives à l'Université Souq Ahras) nous avons utilisé un questionnaire composé de 25 énoncés répartis sur cinq domaines sur mon échantillon (43) professeurs et administrateurs de l'Institut des Sciences et Technologies des Activités Physiques et Sportives, Les données ont été traitées statistiquement avec le Statistical Package for Humanities, version 22, et l'étude a conclu que les retards dans la transformation numérique à l'Institut des sciences et technologies physiques et sportives de l'Université Souq Ahras Jayat sont élevés, et l'étude a également conclu qu'il n'y a pas de différences statistiquement significatives dans le point de vue des professeurs et des administrateurs sur les retards qui entravent la transformation numérique dans l'institut Science et Technologie des Activités Physiques et Sportives de l'Université Souq Ahras Ta'zi pour la variable d'âge et d'emploi (administratif, non administratif), alors qu'il existe des différences statistiquement significatives dans les points de vue des professeurs et des administrateurs sur les obstacles qui retardent la transformation numérique à l'Institut des sciences et technologies des activités physiques et sportives de l'Université Souq Ahras Ta'zi pour la variable de certification et d'expérience professionnelle .
دراسة ميدانية بمعهد سوق أهراس
Keywords: معوقات; التحول الرقمي; الأساتذة، الإداريين; handicaps; digital transformation; professor; administrators; handicap; transformation numérique; les professeurs; administrateurs